Determinants of virological outcome and adverse events in African children treated with paediatric nevirapine fixed-dose-combination tablets. (24th April 2017) - Bienczak, Andrzej; Denti, Paolo; Cook, Adrian; Wiesner, Lubbe; Mulenga, Veronica; Kityo, Cissy; Kekitiinwa, Addy; Gibb, Diana M.; Burger, David; Walker, Ann S.; McIlleron, Helen
Abstract : Background: Nevirapine is the only nonnucleoside reverse transcriptase inhibitor currently available as a paediatric fixed-dose-combination tablet and is widely used in African children. Nonetheless, the number of investigations into pharmacokinetic determinants of virological suppression in African children is limited, and the predictive power of the current therapeutic range was never evaluated in this population, thereby limiting treatment optimization. Methods: We analysed data from 322 African children (aged 0.3–13 years) treated with nevirapine, lamivudine, and either abacavir, stavudine, or zidovudine, and followed up to 144 weeks. Nevirapine trough concentration ( C min ) and other factors were tested for associations with viral load more than 100 copies/ml and transaminase increases more than grade 1 using proportional hazard and logistic models in 219 initially antiretroviral treatment (ART)-naive children. Results: Pre-ART viral load, adherence, and nevirapine C min were associated with viral load nonsuppression [hazard ratio = 2.08 (95% confidence interval (CI): 1.50–2.90, P  < 0.001) for 10-fold higher pre-ART viral load, hazard ratio = 0.78 (95% CI: 0.68–0.90, P  < 0.001) for 10% improvement in adherence, and hazard ratio = 0.94 (95% CI: 0.90–0.99, P  = 0.014) for a 1 mg/l increase in nevirapine C min ]. There were additional effects of pre-ART CD4 + cell percentage and clinical site. The risk of virological nonsuppression decreased with increasing nevirapine C min, and there was no clear C min threshold predictive of virological nonsuppression. Transient transaminase elevations more than grade 1 were associated with high C min (>12.4 mg/l), hazard ratio = 5.18 (95% CI 1.95–13.80, P  < 0.001). Conclusion: Treatment initiation at lower pre-ART viral load and higher pre-ART CD4 + cell percentage, increased adherence, and maintaining average C min higher than current target could improve virological suppression of African children treated with nevirapine without increasing toxicity. Abstract : Supplemental Digital Content is available in the text